Growing use of home enteral nutrition: a great tool in nutrition practice toolbox. Issue 5 (September 2021) - Mohamed Elfadil, Osman; Ewy, Matthew; Patel, Jalpan; Patel, Ishani; Mundi, Manpreet S.
Abstract : Purpose of review: Home enteral nutrition (HEN) is a well-established practical nutrition therapy tool that is typically managed by an interdisciplinary team. Prevalence of HEN is increasing across the globe given significant evidence for utility, feasibility, efficacy, safety, and reliability of HEN in helping patients meeting their nutrition needs. The current review highlights the growing use of HEN in the context of what is novel in the field including trends in HEN practice with regards to tubes and connectors, feeding formula and real food blends, and common complications. The review also highlights that the use of HEN is expected to expand further over coming years emphasizing the need for national consensus recommendations and guidelines for HEN management. Recent findings: The growing use of HEN has always been parallel to adoption of holistic definitions and concept of malnutrition in clinical nutrition practice and more understanding of the need for malnutrition risk stratification, meeting unmet needs in practice and addressing challenges that lead to suboptimal enteral nutrition. Summary: Research and advancements in technology as well as in tube feeding formula industry have led to the development of more solutions and have helped identify and implement best HEN practices.